2022
DOI: 10.1530/jme-21-0263
|View full text |Cite
|
Sign up to set email alerts
|

Personalised medicines for familial hypercalcemia and hyperparathyroidism

Abstract: Loss-of-function calcium-sensing receptor (CaSR) mutations cause the mineral metabolism disorders familial hypocalciuric hypercalcemia or neonatal severe hyperparathyroidism,and increase the risk of femoral fracture, chronic kidney disease, coronary heart disease, and other diseases. In severe cases, CaSR mutations are lethal. Off-label use of the CaSR positive allosteric modulator (PAM), cinacalcet, corrects hypercalcemia in some patients with CaSR mutations. However, other patients remain unresponsive to cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, CASR mutations have been found to cluster in three regions: the second peptide loop of the ECD, the VFT cleft region (eCa 2+ o -binding site), and the region encompassing transmembrane domains (TMD) 6 and 7 ( 5 , 12 ). Intriguingly, FHH1 patients with CASR mutations in different domains exhibit distinct and variable phenotypic severities ( 1 , 11 ). Although one in vitro study showed that calcimimetics can correct the expression in some CASR mutations ( 11 ), research on personalized treatment using calcimimetics for different CASR variants is limited ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, CASR mutations have been found to cluster in three regions: the second peptide loop of the ECD, the VFT cleft region (eCa 2+ o -binding site), and the region encompassing transmembrane domains (TMD) 6 and 7 ( 5 , 12 ). Intriguingly, FHH1 patients with CASR mutations in different domains exhibit distinct and variable phenotypic severities ( 1 , 11 ). Although one in vitro study showed that calcimimetics can correct the expression in some CASR mutations ( 11 ), research on personalized treatment using calcimimetics for different CASR variants is limited ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, FHH1 patients with CASR mutations in different domains exhibit distinct and variable phenotypic severities (1,11). Although one in vitro study showed that calcimimetics can correct the expression in some CASR mutations (11), research on personalized treatment using calcimimetics for different CASR variants is limited (28)(29)(30). In addition, cinacalcet-unresponsive patients might harbor the missense mutations or in-frame deletions of CASR exon 5 encoding amino acids 460-536 in the extracellular domain (ECD) (31,32), indicating that the different CASR mutations are likely responsible for the biodiversity in calcimimetics treatment.…”
Section: Ecd the Vft Cleft Region (Eca 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…This new structural evidence in biochemical and structural determination of the framework of CaSR and its interaction sites with natural ligands, as well as exogenous PAMs and NAMs, further support a coactivation model involving calcium and amino acids for functional cooperativity and provide molecular insights into disease‐related mutations. These key structural determinants in ligand interaction and regulation have the potential to promote rapid development of novel drugs against various calciotropic and noncalciotropic diseases 55,111,273,274 …”
Section: Translational Potential Of Targeting Casr For Human Diseasesmentioning
confidence: 99%
“…These key structural determinants in ligand interaction and regulation have the potential to promote rapid development of novel drugs against various calciotropic and noncalciotropic diseases. 55,111,273,274 Newly developed Ca 2+ sensors, such as R-CatchER and G-CatchER + , are capable of capturing rapid Ca 2+ dynamics in the ER. These new tools will improve our understanding of CaSR-mediated Ca 2+ signaling, the molecular basis of diseases, and functional cooperativity of ligands, as well as facilitate drug discovery.…”
Section: Translational Potential Of Targeting Casr For Human Diseasesmentioning
confidence: 99%